Structural And Spectroscopic Studies On New Pyrene Based Chalcone Derivatives As Potential Solar Cell Materials - Mohd Nizar, Siti Nabilla Aliya (2022)
A series of Pyrenyl Chalcone (PnCh) derivatives have been strategically synthesized for the dye-sensitized solar cell (DSSC) application by proposing different electron donor and acceptor substituent groups. All compounds were successfully synthesized using the Claisen-Schmidt condensation reaction and attained 5 single crystals via slow evaporation method.